Pinch analysis-based approach to industrial safety risk and environmental management - Tan, Raymond Girard R. (Animo Repository, 2016)
Pinch Analysis is an established method for enhancing the sustainability of industrial processes via efficient use of various resources. It is based on the principle of target identification followed by subsequent system design aided by a problem decomposition strategy based on the Pinch Point. This approach has recently been extended to apply to a broad range of structurally analogous problems in various domains, such as financial management and carbon-constrained energy planning. In this work, a novel graphical methodology for industrial safety risk and environmental management is proposed. In this method, it is assumed that a set of risk or pollution reduction measures is available, and that each measure is characterized by its implementation cost and the degree of benefit that it delivers. These data are then used to generate a source composite curve. Targeting can then be achieved by shifting this curve relative to a pre-defined sink composite curve, which represents the locus of the plant management’s “willingness to pay,” or budget relative to benefits with respect to risk or pollutant reduction. The methodology is then demonstrated on two case studies. The first case is based on the well-known Bhopal incident, while the second case focuses on the reduction of airborne fluoride emissions from brick firing plant. © 2016, Springer-Verlag Berlin Heidelberg.